2019
DOI: 10.21475/ajcs.19.13.07.p1662
|View full text |Cite
|
Sign up to set email alerts
|

Phytomass accumulation and mineral composition of cowpea (Vigna unguiculata) under salt stress and phosphate fertilization

Abstract: This study aimed to evaluate the effect of irrigation with saline water and phosphate fertilization on phytomass accumulation and tissue mineral composition of cowpea shoots. The research was carried out in a greenhouse utilizing randomized block design in a 5 x 3 factorial scheme consisting of five levels salinity of irrigation water (0.5 as control, 1.5, 2.5 3.5 and 4.5 dS m-1) and three doses of P2O5- (60, 100 and 140% from a recommended dose of 60 kg P2O5- ha-1), with 5 replicates. The plants were grown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Roxão was the only variety without SDM modifications caused by salinity and was unique in the susceptible group with an investment in biomass at the expense of grain production. The authors in [ 7 , 8 , 24 , 25 ] and other authors observed reduced growth and biomass accumulation in cowpea beans under salt stress. These reductions are part of the acclimation process of cowpea bean plants that have the potential to tolerate salt stress as they seek to secure production and perpetuate the species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Roxão was the only variety without SDM modifications caused by salinity and was unique in the susceptible group with an investment in biomass at the expense of grain production. The authors in [ 7 , 8 , 24 , 25 ] and other authors observed reduced growth and biomass accumulation in cowpea beans under salt stress. These reductions are part of the acclimation process of cowpea bean plants that have the potential to tolerate salt stress as they seek to secure production and perpetuate the species.…”
Section: Discussionmentioning
confidence: 99%
“…The A N reductions were related to stomatal factors, i.e., the reduction of stomatal conductance limited the influx of CO 2 and consequently the internal concentration of CO 2 ( Ci ) in the substomatal cavity, reducing water absorption and transpiration [ 6 , 17 , 18 ]. The reduction of stomatal conductance occurred with increased soil salt concentrations and led to a decrease in osmotic and water potentials, resulting in toxicity of specific ions—Na + and Cl - [ 5 , 8 , 9 ]. Plants experience issues absorbing water from the soil under salt stress and tend to reduce water loss by closing stomates and reducing transpiration [ 6 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations